Women as productive human capital: towards a developed Malaysia - Abd. Rokis, Rohaiza (2009)
This paper develops the issues of human capital development in Malaysia. It specifically examines the position of women as human capital in developing the nation. The paper inclines to state that women workers have priority conflict between home and workplace that may mark down their position as a productive human capital. Mainly based on the interview on thirty-three female professionals at PetCo and four government officers, this paper investigates women work experience alongside the barriers they face at home. The major objective of this study is study the social and cultural environment at work experienced by women. Consequently, this paper highlights some areas that may be helpful to encourage women in expanding their human capital development in developing Malaysia.